Versus: ¿Es posible hablar de error? El error culturalmente condicionado en el Perú - Villavicencio, Felipe; Meini, Iván (Pontificia Universidad Católica del Perú, 2015)
Cultural diversity is one of the biggest challenges that contemporary Law is facing. From this state of things, the penal regulation takes particular relevance, due to its burdensome towards who has committed a crime. A question arises about if it is possible to condemn someone due to the valoration that a different culture made about a specific behavior.In the present versus, there is a discussion about how to understand article 15 of the peruvian Criminal Code, and if the option chosen by the national system of justice is suitable to face the aforementioned problem.

La diversidad cultural es uno de los mayores desafíos que el Derecho contemporáneo afronta. Desde este estado de cosas, cobra particular relevancia laregulación penal, al ser la más gravosa para quien comete un delito. Surge la pregunta sobre si es posible condenar a alguien por la valoración que hizo una cultura que no es la propia de una conducta.En el presente versus, se discute acerca de cómo entender el artículo 15 del Código Penal, y si la opción que ha adoptado el ordenamiento nacional es idónea para abordar el problema mencionado.
Versus: Is it possible to talk about an error? The culturally induced error in the Peruvian legislation
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01